The Effect of Health Education with Audio Visual Media about Sexuality on the Attitudes and Perceptions of Adolescents at SMP N 13 Rejang Lebong Year 2024 - Asmawati, Elmi; Handayani , Tita Septi; Syafrie , Ice Rakizah (Utami Publisher, 2025)
Introduction: Adolescence is a period of transition from childhood to adulthood, during which various changes occur including biological, psychological and social changes (Jose, 2019). Biological changes include physical changes, hormonal changes and sexual behaviour (Geldard & Geldard, 2017). Survey results from the Central Bureau of Statistics and the United Nations Children's Fund (2020), 1 in 9 girls are married in Indonesia, women aged 20-24 years who were married before 18 years in 2018 are estimated to reach around 1,220,900 and this figure puts Indonesia in the 10 highest countries in the world.The purpose of this study is to determine the effect of health education with audio visual media on sexuality on the attitudes and perceptions of adolescents. Method: This type of research is a quasi-experemintal design with the design ‘One Group Pre test-Post test’. Data were collected with the tool used in data collection is a questionnaire. The population in this study were X and XI grade students at SMP N 13 Rejang Lebong, the number of samples was 20 respondents. Results and Discussion: The results of univariate test analysis that the average of 31.00 attitude of adolescents about sexuality before, average of 35.50 attitude of adolescents about sexuality after, average of 21.90 perception of adolescents about sexuality before and average of 39.05 perception of adolescents about sexuality after given Health Education with Audio Visual Media. The results of the bivariate test showed the influence of adolescents' attitudes after being given Health Education with Audio Visual Media about Sexuality with a value at SMP N 13 Rejang Lebong with the results of statistical tests obtained a p value of 0.001. Conclusion: It is expected that schools and health workers can provide health promotion to adolescents about health education about sexuality. This research is expected to be one of the reference materials in the library.